Identifying neuropsychological predictors of drawing skills in elementary school children. Issue 3 (2nd April 2020) - Senese, Vincenzo Paolo; Zappullo, Isa; Baiano, Chiara; Zoccolotti, Pierluigi; Monaco, Marianna; Conson, Massimiliano
ABSTRACT: Much evidence indicates that drawing is related to different neuropsychological abilities in children. However, a comprehensive cognitive model of drawing in children is still lacking. Here, we conducted a study on the neuropsychological predictors of drawing in a sample of 142 typically developing elementary school children ( M age = 8.8 years; SD = 1.1). Based on a path analysis, we examined the contribution of visual perception (matching geometrical figures), complex spatial abilities (e.g., complex figures identification and mental rotation), visual attention, working memory, verbal and visual-motor skills, as well as of gender, age and socio-economic status, to copying the Rey-Osterrieth Complex Figure (ROCF). Results showed that ROCF copying was influenced in a specific and additive way by visual perception, visual-motor coordination, and verbal abilities as well as age, while it was indirectly related to visual attention, working memory, and to complex spatial abilities. These findings provide the grounds for identifying the neuropsychological bases of drawing in elementary school children.